Two new Andean species of Anolis lizard (Iguanidae: Dactyloinae) from southern Ecuador. Issue 13 (30th March 2018) - Torres-Carvajal, Omar; Ayala-Varela, Fernando P.; Lobos, Simón E.; Poe, Steven; Narváez, Andrea E.
ABSTRACT: We describe two new species of Anolis lizard that are sympatric on the Amazonian slopes of the Andes of southern Ecuador at elevations between 1440 and 1970 m. The new species may be distinguished from other Anolis by external anatomy, mitochondrial divergence and dewlap colour. We estimate the phylogenetic positions of the new species using Bayesian analysis of DNA sequence data including all species of Dactyloa -clade Anolis for which DNA data are available. Anolis hyacintogularis sp. nov. is sister to Anolis calimae, whereas Anolis lososi sp. nov. is sister to Anolis williamsmittermeierorum, herein reported for Ecuador for the first time. Individuals of both new species were collected within a protected area in southern Ecuador, Podocarpus National Park, which suggests that at least some populations of these species are well protected. www.zoobank.org/urn:lsid:zoobank.org:pub:E55FA804-E3FD-4412-8FEB-5234E29E272D